Structural Identification of Chemical Constituents from Scutellaria baicalensis by HPLC-ESI-MS/MS and NMR Spectroscopy - Lin, Wenhui; Liu, Shuang; Wu, Bin (Asian Journal of Chemistry, 2013)
Scutellariae Radix, the dried roots of Scutellaria baicalensis Georgi, which is one of the famous herb widely used in the treatment of pyrexia, jaundice and hypertension. To directly identify the compounds of the extract of the S. baicalensis was performed using HPLC-ESI-MS/MS. Chromatographic (analytical and preparative HPLC), chemical (hydrolysis) and spectroscopic (UV, 1H and 13C NMR, MS) techniques were applied for separation, isolation, purification and identification of new compounds. A systematic phytochemical investigantion of S. baicalensis led to the isolation of 7 new and 40 known chemical constituents. By HPLC-ESI-MS/MS and NMR spectral analyses, the new compounds were identified as 7-hydroxy-3,5,8-trimethoxy-3',4'-methylenedioxy flavone-7-O-b-glucopyranoside (1), 7-hydroxy-5,6,8-trimethoxy-3',4'-methylenedioxy flavone-7-O-b-glucopyranoside (2), patuletin-7-b-glucuronide (3), pinobankasin-6-C-glucopyranosyl-8-C-arabinopyranoside (4), chrysin-3-C-a-arabinopyranosyl-8-C-b-glucopyranoside (11), 6-sulfooxy-chrysin-7-glucoside (12) and 5-hydoxy-6,7,4'-trimethoxy-flavanone 5-sulfate (24).